Pengaruh Kelompok Teman Sebaya dan Status Sosial Ekonomi Orang Tua Terhadap Perilaku Konsumtif: Studi pada Mahasiswa Bidikmisi Uin Fas Bengkulu - Yasfa Ilmiah; Uswatun Hasanah; Nurul Hak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of peer groups and parents' socioeconomic status on consumptive behavior (study on Bidikmisi Uin Fas Bengkulu students). To test this, researchers used quantitative methods with primary data collection techniques in the form of questionnaires distributed to 63 respondents. The data analysis technique used is multiple regression analysis with the IBM SPSS 26 application. The results of the study based on the simultaneous hypothesis test (f test) show that the peer group variables and the socioeconomic status of parents simultaneously affect the consumptive behavior of Bidikmisi Uin Fas Bengkulu students, this can be seen in the Fcount value of 8.432 > Ftabel 3.150 and the significance value is 0.001 < 0.05. Furthermore, it can be seen in the results of the coefficient of determination test. Furthermore, it can be seen in the test results of the coefficient of determination (R2) which obtained an Rsquere value of 0.219. This shows that the dependent variable of consumptive behavior can be explained by the independent variable of peer group and socioeconomic status of parents by 21.9% while 78.1% is explained by other factors outside the variables studied.